Co-digestão anaeróbia de microalgas e de glicerol residual do biodiesel - Machado, Francisca Lívia de Oliveira (2012)
Microalgae, microscopic life forms with photosynthetic capacity, produce oxygen thanks to light energy. Due to this capacity, microalgae are used for sewage treatment in stabilization ponds, however, this activity generates a large amount of microalgal biomass. In view of this excess of biomass production and its disposal in water bodies produces unpleasant effects, it has been evaluated the re-use of this biomass as a substrate for methane production in anaerobic digestion. Since microalgae have a rigid cell wall, the application of microalgae hydrolysis tests was necessary in order to improve its biodegradability. Heat pretreatment for 30 minutes at 120°C and 1 kgf/cm2 resulted in the best pretreatment applied. In order to improve C/N ratio, residual glycerol coming from biodiesel production was used to perform co-digestion with microalgae. Residual glycerol coming from biodiesel production (1Kg of glycerol per 10 Kg of biodiesel generated) is an impure residue which is also produced at large scale as a byproduct from the trans-esterification of fats and oils. In fact, the presence of impurities limits its applications. In this study, different COD/N ratios of 20 (phase 2), 40 (phase 3) and 70 (phase 4) were tested and the organic loading rate (OLR) applied ranged from 0,06 to 0,75 kg/m3.d. In the phase 1 only microalgae was used on the influent. Two modified UASB reactors were used. One of them was fed with pretreated microalgae, while the other one was fed with non-pretreated microalgae. Both of them were operated in co-digestion with glycerol. COD removal efficiencies ranged between 40% and 90%. Biogas produced presented values of 73% and 84% for each bioreactor treating pretreated and non-pretreated microalgae, respectively. Neither nitrogen nor ammonia and total and volatile suspended solids was significantly removed. Moreover, microalgae were the sole source of macro and micro-nutrients in this work. Sodium bicarbonate was used as a buffer during the phase 4, since pH fall down enough to harm the anaerobic digestion process at the beginning of phase 4. Based on the maintenance of adequate VFA/Alk ratios, both reactors presented a stable operation, specially the reactors treating pre-treated microalgae. Instability periods were mainly observed in some operation phases in the reactor without pretreatment. Specific methanogenic activity tests were carried out in order to evaluate the quality of the inoculum in terms of activity and methane production. Methane production presented a mean value of 0,26 g DQO-CH4/g SSV.d